Stent Selection in Preoperative Biliary Drainage for Patients With Operable Pancreatic Cancer Receiving Neoadjuvant Therapy: A Meta-Analysis and Systematic Review - Du, Jianbing; Gao, Xiangyu; Zhang, Hongtao; Wan, Zhuo; Yu, Hengchao; Wang, Desheng (Frontiers in Surgery, 2022)
As neoadjuvant therapy (NAT) is increasingly used in patients with pancreatic cancer to reduce the tumor burden in the prognosis, preoperative biliary drainage (PBD) becomes more and more necessary. Aim of this study is to summarize the latest evidence and compare the clinical effectiveness of metal stent (MS) and plastic stent (PS) in patients undergoing preoperative neoadjuvant therapy for resectable pancreatic cancers. Eligible studies were searched in PubMed, Embase and Cochrane Library from their inception to September 2021. In this study, RevMan 5.4 was used to perform the analyses. Two randomized controlled trials (RCTs) and six retrospective studies were included, with 316 patients. All patients had pancreatic cancer, who received NAT before surgical resection. Meta-analysis showed that the rate of endoscopic reintervention was lower in MS (26/143, 18%) than PS (122/153, 80%) group (P < 0.05). The rate of stent-related complications was lower in MS (18/118, 15%) than PS (52/117, 44%) group (P = 0.02). But there were no significant differences between group in operative time, operative blood loss, overall postoperative complications, postoperative hospitalization days and total medical costs. For preoperative biliary drainage in resectable pancreatic cancers patients undergoing NAT, MS was more priority than PS in the rate of endoscopic reintervention and stent-related complications. More clinical trials are required in the future in order to confirm these data with a higher level of evidence.